A self-based phenomenological approach to Gil-gamesh’s dreams - (:unkn) unknown (Universitaet Heidelberg, 2020)
The epic of Gilgamesh is one of the world’s oldest known epics. The aim of this study is to interpret Gil-gamesh’s dreams using the phenomenological method and, through this, reveal Gilgamesh’s experiences and the intentionality of his self. The theoretical resources and stages of the Phenomenological Dream Self Model (PDSM) as well as imaginative variation, which is a phenomenological technique, were used for the interpretation of the dreams in the epic of Gilgamesh. While we examined Gilgamesh’s dream self and wakeful self experiences in the first two stages of our PDSM interpretation, we compared the experiences of both selves in the third stage. In the fourth stage, we revealed the existence and the process of change and development of the feeling of omnipotence at the core of our two chosen dreams of Gilgamesh with using the narrations in the epic. As a result, we contend that both the phenomenological method and PDSM can be utilized in addition to real persons’ dreams with respect to understanding the dreams of the characters in the literary text. © 2020. All Rights Reserved.
Keywords: dream; Epic of Gilgamesh; literary criticism; phenomenological dream-self model (pdsm); phenomenology